Pengaruh Pemberian Pupuk Organik Padat terhadap Pertumbuhan Rumput Odot (Pennisetum purpureum cv. Mott) - Eko Prasetyo; Widiastuti Ardiansyah; Susan Mokoolang; Dewi Shinta Achmad (Pusat Riset dan Inovasi Nasional, 2026)
Odot grass (Pennisetum purpureum cv. Mott) is an important ruminant forage because of its high palatability, adaptability to tropical environments, and potential for high biomass production. This study aimed to evaluate the effect of solid organic fertilizer on the growth and production of odot grass as a basis for developing productive and sustainable forage cultivation. The experiment was conducted in Pangi Village, Dulupi District, Boalemo Regency, from February to March 2026 using a completely randomized design with five treatments and three replications. The treatments consisted of P0 without solid organic fertilizer, P1 at 10 t/ha, P2 at 20 t/ha, P3 at 30 t/ha, and P4 at 40 t/ha. Observed variables included plant height, leaf number, tiller number, and fresh weight production. Data were analyzed using analysis of variance followed by Duncan’s multiple range test at the 5% significance level. The results showed that P4 produced the best response for all measured parameters. The highest plant height was 77.83 ± 43.80 cm, with 18.83 ± 3.67 leaves, 2.42 ± 1.38 tillers, and fresh weight production of 52.33 ± 10.12 t/ha. These improvements indicate that 40 t/ha solid organic fertilizer enhanced nutrient availability and supported biomass formation. Solid organic fertilizer is therefore a promising locally based cultivation input for improving ruminant forage productivity.